Clinical application of a novel rib fracture score system in patients with multiple rib fractures - Zhang, Jianpeng; Li, Weiqiang; Liu, Zhidong (Frontiers in Surgery, 2026)
ObjectivesTo validate a new type of rib fracture score system for treatment decisions in patients with multiple rib fractures.MethodsThis retrospective study included patients admitted with multiple rib fractures from one clinical center between April 2017 and April 2022. Patients were divided into the conservative group and the surgical group based on their management strategy. The patients were assessed using a novel rib fracture score system based on anatomical and pathophysiological characteristics.ResultsIn a study of 564 patients, 290 underwent surgical treatment while 274 received conservative treatment. Surgical patients had significantly higher satisfaction scores (P < 0.001) and a greater prevalence of chronic diseases (P = 0.022). The optimal satisfaction cut-off was 9.5 points, dividing patients into low score (LS, <10) and high score (HS, ≥10) groups. In the LS group, pneumonia incidence was similar (P > 0.05). However, in the HS group, surgical patients experienced lower pneumonia rates (no pneumonia: 76.1% vs. 11.5%, P < 0.001), reduced ventilator hours (8.1 ± 37.6 vs. 23.7 ± 66.7, P < 0.001), and less opioid use (1.2 ± 1.5 vs. 2.7 ± 2.5 times, P < 0.001). For scores ≥15, conservative treatment may lead to increased respiratory complications.ConclusionsClinical application of the novel rib fracture score system may be efficient in stratifying patients with rib fractures. Patients with a score ≥10 may benefit from surgical intervention. Patients with a score ≥15 may have a greater risk of respiratory complications during the period of conservative treatment compared with the LS group, suggesting the importance of surgical intervention in such patients.